Optymalne Sprężanie Ośrodków o Stałej Grubości w Płaskim Stanie Naprężenia - Holnicki-Szulc, J. (Engineering Transactions, 1972)
The medium considered is assumed to be elastic, homogeneous and isotropic. The problem is formulated of such a state of stress resulting from prestressing which would introduce into the system the minimum amount of energy and which, together with the stresses produced by external loads, would not exceed a prescribed value of reduced stress at any point of the region of the layer.The method is also discussed of introducing the stress fields thus determined by means of a suitably shaped, dense lattice of elastic cables. In the second part of the paper are discussed the cases of rotational symmetry of the structure; the solution is illustrated by an example of the Lame problem.